Study of Sucrose and Glucose Syrup Dosages on the Quality of Milk Caramel Candy - Ari Rofiah; Al Machfudz WDP (Universitas Muhammadiyah Sidoarjo, 2014)
Milk has high nutritionalvalue due to its content, such as essential fatty acid, high protein, lactose as brain nutrition and calcium. However, itis perishable food that makesshortershelf-life. Due to its short shelf-life, processing to be the dairy products is method to extend the shelf-life.Milk caramel candy is one of dairy products that hasspesific taste and odor. Aim of this study was to determine and study the concentrations effetct of sucrose and glucose syrup towards the quality of milk caramel candy. Different concentrations of sucrose were 100, 125 and150gram, respectively. Another observation was glucose syrup and its concentrations were30, 40 and50gram.Experiment was designed byfactorialand randomized block design was used in this research. The quality was observed bychemicalanalysis, physical analysisandorganoleptic tests.Statistical analysis wereanalyzed usingANOVA, followed by HonestlySignificant Difference (HSD) 5% and organoleptic test datawasanalyzed byFriedmantest. Concentration ofsucroseandglucosesyrup weresignificantlydifferent on moisture content, reducing sugarcontent, textureandnotsignificantly differenton carbohydrate, fat, andprotein content. Organoleptic datawere significantly different oncolor, flavor, andtextureexceptaroma. The best quality wasmilk caramel candy using 100 gramof sucroseand30 gram ofglucosesyrupwithin its sensory quality werecolorvalueof 3.40, 3.80 for flavor, 3.37 for aroma;3.73 fortexture. Chemical and physical qualities werewater contentof 7.56%;reducing sugarlevels content of19.99%;carbohydrate content of59.62%;fat content of4.42%;protein content of3.04%, andtexture3.87mm/50g/5sec.